The development of automatic forced air egg incubator / Raja Mohd Noor Hafizi Raja Daud ... [et al.] - Raja Daud, Raja Mohd Noor Hafizi; Sidek, Mohd Nazrul; Mat Zain, Mohamad Yusof; Kassim, Abdul Hafiz (2019)
The poultry sector is one of the biggest components of the livestock industry in Malaysia. In recent years, there has been a rise in poultry livestock demand which cannot be fulfilled solely by the domestic supply chain leading them to depend on import in overcoming this problem. In order to maintain the livestock, the egg incubator was introduced in the poultry industry. The aim is the large scale production of poultry livestock through egg incubation process. Since the temperature and humidity can affect the egg's embryo development, this project is equipped with sensors to control the accuracy of temperature and humidity during the egg incubation process. The two main sensors used in this project are temperature sensor and humidity sensor. The temperature sensor controls the lighting on and off of the bulk lamp which acts as the heating element producing heat while the humidity sensor controls the mist spray providing the optimum humidity during the incubation process. Then, the latest readings of temperature and humidity detected by the sensors will be displayed on the LCD display. The eggs will be rotated every 3 hours using the automatic egg turner system driven by the motor and also, a forced air fan is used for ventilation system to circulate the air in the incubator to prevent the egg's embryos mortality.The whole system in the incubator is controlled by a microcontroller called Arduino Uno which is programmed to produce an efficient operation system between the inputs and the outputs.